Dirty pictures [videorecording (DVD)] - Sauret, Etienne; Shulgin, Alexander T. (Alexander Theodore); Shulgin, Ann; Sager, Bob; Nichols, David E., 1944-; Fantegrossi, William; Griffiths, Roland (Breaking Glass Pictures, 2011)
Alexander 'Sasha' Shulgin is the scientist behind more than 200 psychedelic compounds, including MDMA, more commonly known as Ecstasy. Considered to be one of the greatest chemists of the 20th century, Shulgin's vast array of discoveries have had a profound impact in the field of psychedelic research, making him a subject of fascination and controversy among fellow scientists and a folk hero to recreational users of psychedelics.